Programmable CF-OTA-Based Lowpass and Bandpass Filters - Muhammad Taher Abuelma'atti; Azhar Quddus (Active and Passive Electronic Components)
A new circuit is proposed for realizing lowpass and bandpass filter responses. The circuit uses one current-follower and one operational transconductance amplifier. The circuit enjoys low temperature sensitivities, high input impedance and its important parameters are electronically programmable. The use of grounded capacitors is an additional attractive feature for integration. Simulation results confirming the theory presented are included.